Fit-for-purpose based testing and validation of antibodies to amino- and carboxy-terminal domains of cannabinoid receptor 1 - Echeazarra, Leyre; García del Caño, Gontzal; Barrondo, Sergio; González-Burguera, Imanol; Saumell-Esnaola, Miquel; Aretxabala, Xabier; López de Jesús, Maider; Borrega-Román, Leire; Mato, Susana; Ledent, Catherine; Matute, Carlos; Goicolea, María Aranzazu; et al. (Histochemistry and cell biology, 2021)
Specific and selective anti-CB 1 antibodies are among the most powerful research tools to unravel the complex biological processes mediated by the CB 1 receptor in both physiological and pathological conditions. However, low performance of antibodies remains a major source of inconsistency between results from different laboratories. Using a variety of techniques, including some of the most commonly accepted ones for antibody specificity testing, we identified three of five commercial antibodies against different regions of CB 1 receptor as the best choice for specific end-use purposes. Specifically, an antibody against a long fragment of the extracellular amino tail of CB 1 receptor (but not one against a short sequence of the extreme amino-terminus) detected strong surface staining when applied to live cells, whereas two different antibodies against an identical fragment of the extreme carboxy-terminus of CB 1 receptor (but not one against an upstream peptide) showed acceptable performance on all platforms, although they behaved differently in immunohistochemical assays depending on the tissue fixation procedure used and showed different specificity in Western blot assays, which made each of them particularly suitable for one of those techniques. Our results provide a framework to interpret past and future results derived from the use of different anti-CB 1 antibodies in the context of current knowledge about the CB 1 receptor at the molecular level, and highlight the need for an adequate validation for specific purposes, not only before antibodies are placed on the market, but also before the decision to discontinue them is made.